2007
DOI: 10.1097/01.scs.0000248645.10342.2e
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Trauma Resulting From Terror in Israel

Abstract: During a 33 month period, maxillofacial injuries resulting from terrorist attacks in Israel were compared with non-terror trauma maxillofacial injuries. Files of patients hospitalized from October 1, 2000 to June 30, 2003 were obtained from the Israel National Trauma Registry. Data were evaluated and compared with a hospitalized non-terror related trauma population within the same period. A literature survey was also conducted. Terror casualties totaled 1,811. In 493 patients with facial injuries, 322 had soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…In such attacks, the exposed parts of the body, including the face, were affected more than other regions; these results support the studies of other researchers 12,15 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In such attacks, the exposed parts of the body, including the face, were affected more than other regions; these results support the studies of other researchers 12,15 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition to conventional war, the rise of terrorism has added another dimension to the potential for warlike injuries 1 . Other researchers have discussed the injuries caused by terrorism as a separate type of intentional injury 6,15 . The incidence of maxillofacial terrorrelated casualties is high 15 , but there are few studies about this type of injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The three main causes for mouth and jaw fractures are traffic accidents, falls, and violence. 8 In Israel, maxillofacial or dental injuries have been observed in 7.4% of the trauma patients, caused by motor vehicle accidents (39.2%), falls (30.9%), and intentional injuries (21.2%). The most common injuries were soft tissue injuries (55.9%).…”
Section: Discussionmentioning
confidence: 99%
“…8 ' 11 In the series by Ugboko et al, also in Southwestern Nigeria, only one case of gunshot was reported. The male:female ratio of victims of RTA is gradually closing up as more females are becoming more active in recent times exposing them to the danger of RTAs.…”
Section: Okoje © 2010 Prehospital and Disaster Medicinementioning
confidence: 98%